Corneal Epithelial Damage and Impaired Tear Functions in Patients with Inflamed Pinguecula - Erkut Küçük; Uğur Yılmaz; Kürsad Ramazan Zor (Journal of Ophthalmology)
Purpose. In this study, we evaluated corneal epithelial integrity and tear film parameters in patients with inflamed pinguecula and compared these findings with their fellow eyes and with healthy controls. Methods. We evaluated the fluorescein staining properties and performed the tear break-up time (TBUT) test and Schirmer 2 test (ST2) measurements of 32 patients who had symptomatic unilateral inflamed pinguecula and compared the results with their fellow eyes and also with an age- and sex-matched control group. Results. Twenty-three eyes (72%) in the inflamed pinguecula group and 1 eye (3.1%) in the fellow eyes group had punctate epithelial staining (PES) or epithelial defect on the nasal cornea (p<0.001). There was no PES or epithelial defect in the control group. Eyes with inflamed pinguecula (n = 32) had lower TBUT and ST2 values compared to the control group (n = 32) (p<0.001 for both). Fellow eyes (n = 32) also had lower TBUT and ST2 values compared to the control group (p=0.003 for both). There was no difference in the TBUT and ST2 results between the eyes with inflamed pinguecula and fellow eyes (p=0.286 and p=0.951, respectively). Conclusion. A high percentage of eyes with inflamed pinguecula had nasal corneal epithelial staining or epithelial defect. We also found lower TBUT and ST2 results in eyes with inflamed pinguecula and the fellow eyes compared to the control group. These findings may be important in pathogenesis of pinguecula and pterygium and also in uncovering their relation.